IMPORTANCE OF A PROCEDURAL HAND FOR A COMPANY'S ACCOUNTS RECEIVABLE - Tiburcio, Nallely González (IJRDO - Journal of Business Management, 2021)
in this research the issue of accounts receivable will be addressed through a procedure manual which is of great help to companies because it is raised in a systematic way how a procedure will be done and what is the responsibility that should be had in it. The research aims to publicize what accounts receivable are as well as the procedure manual and then describe the importance of having a procedural manual for the area of accounts receivable within the company.